A review of global challenges and survival strategies of small and medium Eeterprises (SMEs) - Sisira Kumara Naradda Gamage; EMS Ekanayake; GAKNJ Abeyrathne; RPIR Prasanna; JMSB Jayasundara; PSK Rajapakshe (Economies, 2020)
Economic globalization has created many challenges for small and medium enterprises (SMEs) due to the rapid increase in competition. Therefore, the downfall rate of SMEs is relatively high, a short period after their commencement. Accordingly, SMEs need to adopt survival strategies and strategic methods to succeed in confronting the various global challenges faced by the SME sector. This study critically examined the existing literature on global challenges for SMEs to understand the SMEs' survival and successive mechanisms in the present competitive business background. Published information related to the field by the multilateral institutions and 110 research papers published by four recognized publishing companies, i.e., Emerald, Elsevier, Taylor and Francis, and MDPI, were chosen for this study. The review revealed the critical global challenges for SMEs within the context of economic globalization. They are the global market competition, global finance and economic crises, information communication technology, the emergence of multi-national corporations, transnational corporations, consumer changes and especially their preferences, trade dumping, international terrorism, and religious conflicts and trade wars. Furthermore, the study considered the survival strategies of SMEs in the industrial platform to recognize sustainability-related policies, specifically, the necessity for a robust theoretical examination on the survival strategies of SMEs in the field of global challenges.
Keywords: 330; economic crisis; global challenges; international terrorism; multi-national corporations; small and medium enterprises; survival strategies; trade war